Reproducible preparation of nanospray tips for capillary electrophoresis coupled to mass spectrometry using 3D printed grinding device. Issue 7 (29th December 2015) - Tycova, Anna; Prikryl, Jan; Foret, Frantisek
Abstract : The use of high quality fused silica capillary nanospray tips is critical for obtaining reliable and reproducible electrospray/MS data; however, reproducible laboratory preparation of such tips is a challenging task. In this work, we report on the design and construction of low‐cost grinding device assembled from 3D printed and commercially easily available components. Detailed description and characterization of the grinding device is complemented by freely accessible files in stl and skp format allowing easy laboratory replication of the device. The process of sharpening is aimed at achieving maximal symmetricity, surface smoothness and repeatability of the conus shape. Moreover, the presented grinding device brings possibility to fabricate the nanospray tips of desired dimensions regardless of the commercial availability. On several samples of biological nature (reserpine, rabbit plasma, and the mixture of three aminoacids), performance of fabricated tips is shown on CE coupled to MS analysis. The special interest is paid to the effect of tip sharpness.